PYODERMA ASSOCIATED WITH ALLERGODERMATOSIS, ASSESSMENT OF THE QUALITY OF THERAPY - Achilova, Feruza Axtamovna; Jalilov, Asliddin Xolmatovich; Islamov, Nurali Hikmatovich (GOLDEN BRAIN, 2024)
The study analyzes modern concepts of etiology, pathogenesis, and treatment of vulgar acne associated with allergic skin diseases. Particular attention was paid to the central role of local manifestations leading to the appearance of acne in a cascade of hormonal, immunological and microbiological changes. As described in the treatment of acne, evidence-based medical approaches are used to determine the most effective treatment.